An Experimental Analysis of the Effects of Non‐audit Services on Auditor Independence in Appearance in the European Union: Evidence from Germany. (June 2015) - Quick, Reiner; Warming‐Rasmussen, Bent
Abstract The provision of non‐audit services by the statutory auditor may have a negative impact on auditor independence. Therefore, the European Union decided to prevent auditors from offering a significant extent of non‐audit services to audit clients. Prior research has revealed that different advisory services have different effects on perceived auditor independence. This could be caused by differences in number and intensity of independence threats (self‐interest, familiarity, self‐review, advocacy). Therefore, this experimental study investigates the effect of such threats on independence perceptions in the case of German individual investors. Multivariate analyses indicate that a high self‐interest and a high‐familiarity threat may impair auditor independence in appearance. On the other hand, our findings do not reveal a significant effect of an existing advocacy threat on investors' trust in auditor independence. A negative effect of a self‐review threat is not directly confirmed. However, the provision of services with regard to internal controls, and thus the self‐review threat, interacts with the self‐interest threat. They potentially impact perceived auditor independence negatively when non‐audit fees are high. In contrast, no significant interactions with familiarity are found. Based on these findings, a general prohibition of non‐audit services does not seem to be necessary. On the other hand, a non‐audit fees cap might be reasonable.